The Effect of Effleurage Massage Technique on Reducing the Scale of Uterine Involution Pain in First Day of Postpartum Mothers in the Working Area of Cikadu Health Center, Cianjur Regency, Indonesia - Leni Herlina; Handayani, Teti Yuli (Arkus, 2023)
The effleurage technique can increase blood circulation to the area being massaged. Increasing blood flow to the uterus and lower abdominal area can help in postpartum recovery and reduce the pain of uterine involution. This study aimed to determine the effect of effleurage massage techniques on reducing the scale of uterine involution pain in postpartum mothers on day 1 in the Cikadu Health Center Working Area, Cianjur Regency, Indonesia. This research is an experimental study with a one-group pretest-posttest design approach. It uses primary data obtained using an assessment instrument, the numeric rating scale (NRS), to determine the level of back pain in pregnant women. A total of 30 research subjects participated in this study. This study shows that effleurage massage intervention effectively reduces the intensity of uterine involution pain in postpartum mothers. There was a decrease in pain intensity after massage effleurage, and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of the effleurage massage technique on reducing the scale of uterine involution pain in postpartum mothers on day 1 in the Cikadu Health Center Working Area, Cianjur Regency, Indonesia